2016
DOI: 10.1177/0969733016638146
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of moral courage in nursing: A hybrid model

Abstract: Moral courage is a pure and prominent characteristic of human beings. The antecedents of moral courage include model orientation, model acceptance, rationalism, individual excellence, acquiring academic and professional qualification, spiritual beliefs, organizational support, organizational repression, and internal and external personal barriers. Professional excellence resulting from moral courage can be crystallized in the form of provision of professional care, creating peace of mind, and the nurse's decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 15 publications
2
97
0
9
Order By: Relevance
“…En general, las acciones de los componentes tanto de este estudio como del EIO 14 son visibles e invisibles y difíciles de cuantificar con probable escaso valor para quienes desarrollan o gestionan los servicios y generalmente son advertidos por su ausencia. Pacientes, familiares o comunidad son considerados con sus necesidades como seres únicos como eje de una atención culturalmente competente y compasiva 28,29 . Sin embargo, la invisibilidad de las acciones de compasión puede tener implicaciones significativas para su reconocimiento, promoción y evaluación en la práctica 9,20 .…”
Section: Discussionunclassified
“…En general, las acciones de los componentes tanto de este estudio como del EIO 14 son visibles e invisibles y difíciles de cuantificar con probable escaso valor para quienes desarrollan o gestionan los servicios y generalmente son advertidos por su ausencia. Pacientes, familiares o comunidad son considerados con sus necesidades como seres únicos como eje de una atención culturalmente competente y compasiva 28,29 . Sin embargo, la invisibilidad de las acciones de compasión puede tener implicaciones significativas para su reconocimiento, promoción y evaluación en la práctica 9,20 .…”
Section: Discussionunclassified
“…Positive effects of courage are empowerment and increased self‐knowledge . In nursing, moral courage can help nurses overcome barriers and promote trust, compassion, hopefulness, and patient safety . As apparent in the case provided, trust was established between the preceptor and the student.…”
Section: Consequences Of Student Couragementioning
confidence: 97%
“…Though literature demonstrating the importance and role of moral courage exists, including in nursing students, effective ways to foster moral courage has been understudied and underreported in the literature. In one analysis, revealed that acquiring academic and professional qualification is an antecedent for moral courage. In other words, students may not exhibit moral courage until they have transitioned into their role as a licensed nurse.…”
Section: Courage In Nursingmentioning
confidence: 99%
“…Stress, anxiety, fear of being scolded, and rejection by colleagues and seclusion are some of the negative consequences that may be created by moral courage [15]. Moral courage helps nurses overcome many barriers like fear, thence enabling them to defend the patient effectively [16]. In their study, Day reported the rate of moral courage as low in healthcare settings and mentioned many factors such as lack of occupational certainty as barriers to nurses' inclination for brave behaviors [17].…”
Section: Introductionmentioning
confidence: 99%